2019
DOI: 10.1155/2019/6728694
|View full text |Cite
|
Sign up to set email alerts
|

TNFAIP3 Gene Polymorphisms in Three Common Autoimmune Diseases: Systemic Lupus Erythematosus, Rheumatoid Arthritis, and Primary Sjogren Syndrome—Association with Disease Susceptibility and Clinical Phenotypes in Italian Patients

Abstract: Autoimmune diseases (AIDs) are complex diseases characterized by persistent or recurrent inflammation, alteration of immune response, and production of specific autoantibodies. It is known that different AIDs share several susceptibility genetic loci. Tumor necrosis factor alpha inducible protein 3 (TNFAIP3) encodes the ubiquitin-modifying enzyme A20, which downregulates inflammation by restricting NF-κB, a transcription factor that regulates expression of various proinflammatory genes. Variants in TNFAIP3 gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 33 publications
2
26
0
3
Order By: Relevance
“…Moreover, we observed that the TT genotype frequency was lower, while the GT genotype frequency was higher in rs2230926, which is a nonsynonymous variant and leads to a change of the A20 protein at residue 127 from phenylalanine to cysteine [37]. Previous studies also reported similar observations concerning the risk association of scleritis with the G allele and GT genotype, such as RA [38], SLE [28,39], and primary immune thrombocytopenia (IPT) [40]. Furthermore, the expression of A20 mRNA was higher in rs2230926 GT genotype as compared to TT genotype carriers [41].…”
Section: Discussionsupporting
confidence: 77%
“…Moreover, we observed that the TT genotype frequency was lower, while the GT genotype frequency was higher in rs2230926, which is a nonsynonymous variant and leads to a change of the A20 protein at residue 127 from phenylalanine to cysteine [37]. Previous studies also reported similar observations concerning the risk association of scleritis with the G allele and GT genotype, such as RA [38], SLE [28,39], and primary immune thrombocytopenia (IPT) [40]. Furthermore, the expression of A20 mRNA was higher in rs2230926 GT genotype as compared to TT genotype carriers [41].…”
Section: Discussionsupporting
confidence: 77%
“…4 Previous studies have related to the IFIH1, TNFAIP3, and STAT4 polymorphisms with a variety of inflammatory and autoimmune disorders such as multiple sclerosis, type 1 diabetes, psoriasis, inflammatory diseases, and SLE. [18][19][20][21][22][23] IFIH1 is found in various immune system cells and is involved in autoimmune disorders such as SLE. 24 IFIH1 increased IFN production by activation of NF-kB, IFNregulatory factors 3 and 7.…”
Section: Discussionmentioning
confidence: 99%
“…An additional similarity was encountered regarding another central inflammatory mediator, the TNF-a. Ciccacci et al studying the role of TNF-a inducible protein 3 (TNFAIP3), an inflammation down-regulating gene, reported its pathogenetic role in all three diseases [ 53 ].…”
Section: Discussionmentioning
confidence: 99%